Assessment and management of children with head injury: practice and opinion. (2nd February 2023) - Proctor, Alyesha; Voss, Sarah; Lyttle, Mark; Benger, Jonathan
Abstract : Background: Head injury is common in children with approximately 700 000 attendances at emergency departments annually; one-third are conveyed by ambulance. However, 75% of them are discharged with no treatment. Most head-injured children could be managed on scene. Aim: This study aimed to investigate paramedic assessment and management of children with minor head injury. Methods: A web-based survey of paramedics at one trust was carried out, and simple descriptive analysis was completed. Findings: Fifty-nine paramedics took part. Parental anxiety, mechanism of injury, presence of red flags, fear of consequences and safeguarding concerns were the most common reasons that paramedics convey children with head injury to the emergency department. Paramedics employ a variety of non-validated tools to help them assess and manage children with head injury, with the head injury guidance by the National Institute for Health and Care Excellence most used. A lack of confidence in wound closure was a key barrier to managing patients on scene, along with a perceived inability to manage children in general, limited GP availability, a lack of training in paediatrics and risk avoidance. Conclusions: Several factors inhibit the ability of paramedics to manage children with minor head injury on scene, leading to avoidable hospital conveyance. Three-quarters of paramedics said they would benefit from a clinical decision tool to support them in the assessment and management of children with minor head injury.